Islamic Boarding School Education and the Relevance of Jihad Fiqh in the Book Fathul Mu'in an Effort to Promote Moderate Islamic Teachings - Deny Kurniawan; Yuani Rohmatin (Global Education Journal, 2026)
Islamic boarding schools and Islamic books are inseparable in contributing to Islamic education in Indonesia, fostering a human civilization that upholds humanitarian values, thus safeguarding life, reason, religion, lineage, and property. Islamic books are sources of knowledge that can maintain diversity in a pluralistic society. One such book that discusses the jurisprudence of jihad isFathul Mu'in, a book written by Shaykh Zainuddin Abdul Aziz Al Malibari Al Fanani and narrated by Sayyid Abi Bakr Syatho with his essay I'anatu At Tholibinreviews one chapter that is worthy of academic scrutiny, namely the Jihad chapter which reviews the meaningAl QitaalIn the perspective of jihad, which is still relevant today, namely the law of jihad and the forms of jihad. Moreover, this book provides the meaning of the purposeAl QitalisAl Hidayahnot war, and able to implement jihad methods that are not extreme and maintain the five main principles of religion. This research islibrary researchwith the main bookFathul Muin and the explanation is the book Ianatu Attholibinespecially in the chapter on jihad as the main reference in searching for data, then reducing the data and analyzing and concluding it using the analysis methodtext interpretationThis research indicates that the yellow books taught in Islamic boarding schools are capable of addressing religious issues to this day. This provides a source of confidence that Islamic boarding schools and their yellow books are capable of addressing the challenges of the times and the problems of life in the archipelago